Integrating Qur’an and Integer Learning in Developing Electronic Students’ Worksheet through Problem-Based Learning - Roy, La; Pepkolaj, LekÃ«; Prahmana, Rully Charitas Indra (AlphaMath : Journal of Mathematics Education, 2024)
Despite the growing interest in contextualizing mathematics education, research integrating Qur’an contexts into mathematics instruction remains limited. Prior studies have largely concentrated on conventional teaching methods, Qur’an-centered instruction, or Problem-based Learning (PBL) as independent approaches. This study addresses a critical gap by integrating Qur’an contexts into integer learning, supported by problem-based learning and facilitated through a technology-enhanced Electronic Student Worksheet (E-SW). The primary objective of this study is to design and assess the reliability and applicability of a Quran-based E-SW using the PBL framework for teaching integers to 7th-grade junior high school students. Employing a Research and Development (R&D) methodology with the ADDIE development model—comprising analysis, design, development, implementation, and evaluation phases—this research utilizes expert validation sheets and student practicality questionnaires as instruments. The study sample consists of 7th-grade students from SMP IT LHI Yogyakarta, with class 7B selected through purposive sampling. Validation results indicate that the E-SW meets established validity criteria, with scores from subject matter and media experts reaching 99 and 91, respectively, both classified as "Good." Practicality testing revealed positive student responses, yielding a practicality score of 61, categorized as "Practical." Furthermore, a paired sample t-test demonstrated a statistically significant improvement in student performance between pretest and posttest results, with a significance (2-tailed) value below 0.05 and an average N-Gain score of 0.4391, which is classified as moderate. These findings suggest that the Quran-based E-SW, structured around the PBL model, effectively enhances students' problem-solving abilities and is suitable for educational use.